Targeting strategies and nanocarriers in vaccines and therapeutics - Khan, Saifur Rahman; Ganguly, Advaita; Malabadi, Ravindra B.; Sunwoo, Hoon H.; Parashar, Archana; Teixeira da Silva, Jaime A.; Suresh, Mavanur R. (Research in Biotechnology, 2011)
In the past few decades, remarkable advances have been made in the field of immunology and molecular biology. Even though the efficacy level, protein binding capacity and other pharmacological parameters are extraordinary, formulations have become more challenging in terms of making drugs or antigens reach specific sites of action, the release rate of a drug at the site of action, proper presentation of an antigen by antigen-presenting cells or dendritic cells and other pharmacokinetic and pharmacodynamic parameters of finished drug products and vaccines. The purpose of this review is to present a brief overview of the challenges to drug targeting, especially vaccines, as well as of different approaches designed to overcome these barriers.